Patterns of Occurrence of Sharks in Sydney Harbour, a Large Urbanised Estuary. - Amy F Smoothey; Charles A Gray; Steve J Kennelly; Oliver J Masens; Victor M Peddemors; Wayne A Robinson (PLoS ONE, 2016)
Information about spatial and temporal variability in the distribution and abundance of shark-populations are required for their conservation, management and to update measures designed to mitigate human-shark interactions. However, because some species of sharks are mobile, migratory and occur in relatively small numbers, estimating their patterns of distribution and abundance can be very difficult. In this study, we used a hierarchical sampling design to examine differences in the composition of species, size- and sex-structures of sharks sampled with bottom-set longlines in three different areas with increasing distance from the entrance of Sydney Harbour, a large urbanised estuary. During two years of sampling, we obtained data for four species of sharks (Port Jackson, Heterodontus portusjacksoni; wobbegong, Orectolobus maculatus; dusky whaler, Carcharhinus obscurus and bull shark, Carcharhinus leucas). Only a few O. maculatus and C. obscurus were caught, all in the area closest to the entrance of the Harbour. O. maculatus were caught in all seasons, except summer, while C. obscurus was only caught in summer. Heterodontus portusjacksoni were the most abundant species, caught in the entrance location mostly between July to November, when water temperature was below 21.5°C. This pattern was consistent across both years. C. leucas, the second most abundant species, were captured in all areas of Sydney Harbour but only in summer and autumn when water temperatures were above 23°C. This study quantified, for this first time, how different species utilise different areas of Sydney Harbour, at different times of the year. This information has implications for the management of human-shark interactions, by enabling creation of education programs to modify human behaviour in times of increased risk of potentially dangerous sharks.